The cult of saints and the Virgin Mary in medieval Scotland - Boardman, Stephen I.; Williamson, Eila (Studies in Celtic history, 2010)
A new investigation of the saints' cults which flourished in medieval Scotland, fruitfully combining archaeological, historical, and literary perspectives.